Consensus on Medical Nutrition Therapy for Diabesity (CoMeND) in Adults: A South Asian Perspective - Kapoor N (Dove Medical Press, 2021)
Nitin Kapoor,1,2 Rakesh Sahay,3 Sanjay Kalra,4 Sarita Bajaj,5 Arundhati Dasgupta,6 Dina Shrestha,7 Guru Dhakal,8 Mangesh Tiwaskar,9 Manisha Sahay,10 Noel Somasundaram,11 Ravinder Reddy,12 Saptarshi Bhattacharya,13 Vijaya Bhaskar Reddy,14 Vijay Viswanathan,15 Dharini Krishnan,16 Manash Baruah,17 A K Das18 1Department of Endocrinology, Christian Medical College, Vellore, Tamil Nadu, India; 2Non Communicable Disease Unit, The Nossal Institute for Global Health, Melbourne School of Population and Global Health, University of Melbourne, Melbourne, Victoria, Australia; 3Department of Endocrinology, Osmania MedicalA30 College, Hyderabad, Telangana, India; 4Department of Endocrinology, Bharti Hospital, Karnal, Haryana, India; 5Department of Medicine, Moti Lal Nehru Medical College, Allahabad, Uttar Pradesh, India; 6Department of Endocrinology, Rudraksh Superspecialty Hospital, Siliguri, West Bengal, India; 7Department of Endocrinology, Hospital for Advanced Medicine and Surgery (HAMS), Kathmandu, Nepal; 8Department of Medicine, Khesar Gyalpo University of Medical Sciences, Thimphu, Bhutan; 9Department of Diabetology, Shilpa Medical Research Centre, Mumbai, Maharashtra, India; 10Department of Nephrology, Osmania Medical College and Osmania General Hospital, Hyderabad, Telangana, India; 11Department of Endocrinology, National Hospital of Sri Lanka, Colombo, Sri Lanka; 12Department of Gastroenterology, CARE Super Specialty Hospital & Transplant Centre, Hyderabad, Telangana, India; 13Department of Endocrinology, Max Superspeciality Hospital, Delhi, India; 14Department of Endocrinology, Government General Hospital, Pondicherry, India; 15Department of Medicine, M.V. Hospital for Diabetes & Prof M Viswanathan Diabetes Research Centre, Chennai, Tamil Nadu, India; 16Department of Food, Nutrition and Dietetics, Laksha Hospitals, Chennai, Tamil Nadu, India; 17Department of Endocrinology, Excel Care Hospitals, Guwahati, Assam, India; 18Department of Medicine, JIPMER, Puducherry, IndiaCorrespondence: Sanjay KalraBharti Hospital, Kunjpura Road, Model Town, Near State Bank of India, Sector 12, Karnal, Haryana, 132001 Tel +91 9896048555Email brideknl@gmail.comAbstract: Diabetes and obesity are both increasing at a fast pace and giving rise to a new epidemic called diabesity. Lifestyle interventions including diet play a major role in the treatment of diabetes, obesity and diabesity. There are many guidelines on dietary management of diabetes or obesity globally and also from South Asia. However, there are no global or South Asian guidelines on the non-pharmacological management of diabesity. South Asia differs from the rest of the world as South Asians have different phenotype, cooking practices, food resources and exposure, medical nutrition therapy (MNT) practices, and availability of trained specialists. Therefore, South Asia needs its own guidelines for non-pharmacological management of diabesity in adults. The aim of the Consensus on Medical Nutrition Therapy for Diabesity (CoMeND) in Adults: A South Asian Perspective is to recommend therapeutic and preventive MNT in the South-Asians with diabesity.Keywords: diabesity guidelines South Asia, medical nutrition therapy South Asia, nutrition therapy for obesity, nutrition therapy for diabetes, diabetes, obesity and diabesity